2020
DOI: 10.24014/ejpe.v3i2.11008
|View full text |Cite
|
Sign up to set email alerts
|

Penggunaan Bahan Ajar Digital Berbasis Inquiry pada Masa Pandemi Covid-19 untuk Mata Kuliah Pembelajaran IPA di SD Kelas Tinggi

Abstract: This study aims to determine the benefits of using inquiry-based digital teaching materials during the Covid-19 pandemic for natural science learning subjects in high-grade elementary schools. The method used in this research is descriptive method with the aim of obtaining a description of the usefulness of digital teaching materials in online learning for elementary school teacher education (PGSD) students. Digital teaching materials are one of the solutions that can be given to problems that occur during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
5
0
2
Order By: Relevance
“…The integration of ICT into the learning process can be realized by presenting innovative ICT-based teaching materials that have not previously been developed in schools. Considering that innovation through the integration of ICT into the learning process is also aimed at preparing human resources that can compete in the current global era (Permana P & Manurung, 2020;Wahyuni et al, 2022), because through the integration of ICT into learning aspects, has been shown to be able to contribute positively to the development and quality of education (Hoerunnisa et al, 2019;Siregar & Marpaung, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The integration of ICT into the learning process can be realized by presenting innovative ICT-based teaching materials that have not previously been developed in schools. Considering that innovation through the integration of ICT into the learning process is also aimed at preparing human resources that can compete in the current global era (Permana P & Manurung, 2020;Wahyuni et al, 2022), because through the integration of ICT into learning aspects, has been shown to be able to contribute positively to the development and quality of education (Hoerunnisa et al, 2019;Siregar & Marpaung, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Bahan ajar dapat memudahkan guru menyampaikan materi di kelas dan melaksanakan kegiatan pembelajaran, sehingga tujuan pembelajaran dapat tercapai dengan baik. Pesatnya perkembangan teknologi digital telah memberi pengaruh besar terhadap dunia pendidikan salah satunya memanfaatkan teknologi digital dalam kegiatan pembelajaran dalam bentuk bahan ajar digital (Kiriana, 2021;Permana P & Manurung, 2020). Dengan adanya kemajuan teknologi, bahan ajar dapat dikemas menjadi bahan ajar digital yang lebih efektif dan efisien (Hasanah et al, 2021;Mudiartana et al, 2021).…”
Section: Pendahuluanunclassified
“…Selain itu, bahan ajar digital dapat membuat siswa aktif dalam proses pembelajaran, efektif dalam kegiatan pembelajaran daring. Siswa perlu suatu media yang disenangi yang dapat membangkitkan kemandirian belajar (Permana P & Manurung, 2020;Ruhiat & Djumena, 2019). Penggunaan bahan ajar digital digital dapat menjadi solusi untuk membuat siswa tertarik belajar dan berperan untuk meningkatkan kemandirian belajar siswa.…”
Section: Pendahuluanunclassified
“…Constraints in the implementation of online learning are caused by students' difficulty adapting and teachers who are not ready to suddenly carry out learning activities (Fauzy & Nurfauziah, 2021). The study result show that teachers have not been able to provide digital learning tools, and the learning process that has taken place has not been systematic because of the unavailability of teaching materials so that the increase in students' abilities related to learning is minimal (Permana P & Manurung, 2020). Therefore, using and utilizing information and communication technology in learning can support and develop cognitive, affective, and social skills (Ganefri et al, 2017).…”
Section: Introductionmentioning
confidence: 99%